Biomechanical adaptations in kayakers of different competitive levels and the relationship with the kayak elements - Abelleira-Lamela T.; Vaquero-Cristóbal, R.; Esparza-Ros, F.; Marcos-Pardo, P. J. (Applied Sciences, 2020)
A paddler`s characteristics can condition the placement of the elements of the boat. The aim of this study was to analyze the differences among kayakers from different skill levels on their sagittal spine position, hamstring extensibility and anthropometric variables; and to determine which variables could be used to determine the arrangement of the elements in the kayak. Thirty-four male sprint kayakers (8 Olympic-level, 13 from the U-23 national team and 13 amateurs) participated in this study. Anthropometric variables, following the protocol of the International Society for the Advancement of Kinanthropometry (ISAK); hamstring extensibility, with active and passive straight leg raise test; sagittal spine position in standing position and in the kayak, and the arrangement of the elements of the boat were measured. The groups with a high skill level showed a lower pelvic tilt in attack position in the kayak than amateurs (p = 0.001). The U-23 group had a lower hamstring extensibility than amateurs (p = 0.053-0.013). The distance from the footrest to the different parts of the seat were dependent on the iliospinale measurement (R = 0.896-0.912). In conclusion, there were differences among groups on the sagittal spine position and hamstring extensibility. In addition, the placement of the boat elements was dependent on anthropometric variables, but not on hamstring extensibility or sagittal spine position.